2006
DOI: 10.1177/0269216306072553
|View full text |Cite
|
Sign up to set email alerts
|

Towards using administrative databases to measure population-based indicators of quality of end-of-life care: testing the methodology

Abstract: This study is concerned with methods to measure population-based indicators of quality end-oflife care. Using a retrospective cohort approach, we assessed the feasibility, validity and reliability of using administrative databases to measure quality indicators of end-of-life care in two Canadian provinces. The study sample consisted of all females who died of breast cancer between 1 January 1998 and 31 December 2002, in Nova Scotia or Ontario, Canada. From an initial list of 19 quality indicators selected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 39 publications
3
103
2
Order By: Relevance
“…Those outcomes were selected because, in prior studies, a shorter interval from diagnosis to death [16][17][18][19]22,23 and in-hospital death 18,20,21 were indicators of lower rates of access to out-of-hospital palliative support. Other outcome indicators of the quality of community-based palliative care at end of life are timely enrolment in specialized palliative care 16,20,23 , no or few days in hospital in the last month of life 18,22 , and minimal use of the emergency department [18][19][20][21][22] . Receiving palliative radiation [16][17][18][19][20]23 and home care [20][21][22] have also been used as indicators of quality end-of-life care.…”
Section: Strengths Limitations and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Those outcomes were selected because, in prior studies, a shorter interval from diagnosis to death [16][17][18][19]22,23 and in-hospital death 18,20,21 were indicators of lower rates of access to out-of-hospital palliative support. Other outcome indicators of the quality of community-based palliative care at end of life are timely enrolment in specialized palliative care 16,20,23 , no or few days in hospital in the last month of life 18,22 , and minimal use of the emergency department [18][19][20][21][22] . Receiving palliative radiation [16][17][18][19][20]23 and home care [20][21][22] have also been used as indicators of quality end-of-life care.…”
Section: Strengths Limitations and Recommendationsmentioning
confidence: 99%
“…Other outcome indicators of the quality of community-based palliative care at end of life are timely enrolment in specialized palliative care 16,20,23 , no or few days in hospital in the last month of life 18,22 , and minimal use of the emergency department [18][19][20][21][22] . Receiving palliative radiation [16][17][18][19][20]23 and home care [20][21][22] have also been used as indicators of quality end-of-life care. Access to, and continuity of, primary care, the use of medical oncology and chemotherapy [18][19][20]22 , and being a nursing home resident 19,23,30 are also relevant.…”
Section: Strengths Limitations and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate pain control and dying in the preferred location are characteristics of quality palliative care 41,42 and of a "good death." 43,44 We found that enrollment in a PCP was associated with filling an opioid prescription in the community.…”
Section: Discussionmentioning
confidence: 99%